IMPACT ANALYSIS BEFORE AND AFTER THE COVID-19 PANDEMIC: THE INFLUENCE OF PROFITABILITY, LIQUIDITY AND SOLVENCY ON COMPANY VALUE IN ISLAMIC JAKARTA INDEX 70 PERIOD 2018-2023 - Roy Satria O. Sunggu; Iskandar Muda; Sirojuzilam (CV. Radja Publika, 2024)
This research aims to determine and analyze the influence of profitability, liquidity and solvency on company value in the Jakarta Islamic Index 70 for the 2018-2023 period. Apart from that, this research also aims to find out whether there are significant differences in profitability, liquidity, solvency and company value in the period before and after the Covid-19 Pandemic. This research is quantitative causality research, namely research that aims to determine causal relationships. The population in this research are companies that are members of the Jakarta Islamic Index 70 (JII70) for the 2018-2023 period. Based on the purposive sampling technique, it can be seen that the number of samples used in this research was 25 companies. The data analysis method in this research was carried out using Panel Data Regression Analysis and Paired t-Test (Difference Test) with the help of STATA software. The results obtained in this research indicate that profitability and solvency have a positive and significant influence on company value. Meanwhile, liquidity has a negative and significant influence on company value in companies that are members of the Jakarta Islamic Index 70 (JII70) for the 2018-2023 period. Other results in this research show that there are no significant differences in profitability, liquidity and solvency in the period before and after the Covid-19 pandemic in companies that are members of the Jakarta Islamic Index 70 (JII70).